Al-Ghazali’s Islamic ethics as a moderator of human capital-performance relationship - Sakinah, Mat Zin; Ahmad Azrin, Adnan; Abdul Malek, A. Tambi (Medwell Journals, 2017)
While the Human Capital (HC) perspective has been widely applied to research in conventional aspects, less attention has been paid to Islamic approach This exploratory study aims to investigate the association between HC and organizational performance, moderated by Islamic ethics, In Islam, entrepreneurs are advised to search for the needed knowledge for human capital development and manage it comprehensively towards the betterment in this world and the hereafter. The study scrutinizes the researches of Al-Ghazali which is based co Sufism (incorporation of Al-gran and Hadith interpretations with reason). Al-Ghazali's thought depicts Islamic ethics that offer practical implications for entrepreneurial activities. What is the effect of human capital on firm performance. Following Islamic business ethics by Al-Ghazali will entrepreneurs with HC be successful. Established on previous contributions in this stream of literature, the present study is pursuing to provide conclusive evidence of the relationship between human capital and fun performance as impacted by Al-Ghazali's Islamic ethics.